2005
DOI: 10.1097/01.rli.0000175037.15022.85
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Magnetic Resonance Imaging of the Small and Large Bowel Using Intraluminal Dual Contrast Technique With Iron Oxide Solution and Water in Magnetic Resonance Enteroclysis

Abstract: Comprehensive MR imaging of SB and LB with DCT improves the identification of modified anatomy and most pathologies in inflammatory and postsurgical bowel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 32 publications
2
19
0
Order By: Relevance
“…Regarding the MRE technique, this and previous studies in our IBD cohort [6,12,14] have shown the high diagnostic value in small-bowel assessment in CD, particularly for the detection of extraluminal pathology such as internal fistulas or a characterization of inflammatory or fibrostenotic complications. MRE has the potential comprehensively to investigate the entire small-and large bowel in one session and therefore provides information on all intestinal segments even in the presence of multiple stenoses and particularly in segments inaccessible to endoscopy.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Regarding the MRE technique, this and previous studies in our IBD cohort [6,12,14] have shown the high diagnostic value in small-bowel assessment in CD, particularly for the detection of extraluminal pathology such as internal fistulas or a characterization of inflammatory or fibrostenotic complications. MRE has the potential comprehensively to investigate the entire small-and large bowel in one session and therefore provides information on all intestinal segments even in the presence of multiple stenoses and particularly in segments inaccessible to endoscopy.…”
Section: Discussionmentioning
confidence: 94%
“…In particular, magnetic resonance enteroclysis (MRE) has provided a remarkable new quality of small-bowel visualization, providing high sensitivity and specificity in the identification of inflammatory stenoses, strictures, or fistulas [6,11,12,14]. However, CE and MRE are somewhat limited while only providing images rather than the possibility of biopsy sampling thus allowing histological proof of CD.…”
Section: Introductionmentioning
confidence: 98%
“…MR enteroclysis requires extensive patient preparation and should be performed utilizing an intraabdominal tube for complete distension of the small bowel loops [21]. Therefore, it is not well tolerated and accepted by patients Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This can be used to prevent overlapping in magnetic resonance cholangiopancreatography (MRCP), for better delimitation with respect to structures adjacent to the bowel (e. g. lymph nodes or uterus) and the evaluation (postoperative) of anatomical changes to the bowel [86], as well as for the detection of inflammatory bowel lesions after i. v. administration [87].…”
Section: Imaging Of the Gastrointestinal Tractmentioning
confidence: 99%